Solomon Islands : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Solomon Islands. (IMF Staff Country Reports; Country Report, 2018)
Solomon Islands has made substantial progress since the Tensions in the early 2000s but faces considerable economic and governance challenges and is highly vulnerable to natural disasters. The logging industry confronts depletion and new sources of growth are needed. Governance challenges are significant, stemming from weak oversight of the resource sectors, a lack of transparency and a need to strengthen public financial management.